1979
DOI: 10.1037/h0077623
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of male mouse (Mus musculus) ultrasonic vocalizations: I. Urinary cues.

Abstract: Eighteen experiments examined the physical characteristics and physiological modulation of the ultrasound-eliciting property of female urine. Experiments 1 and 2 indicated that an excitatory factor exists in female urine and that male urine is essentially neutral with regard to ultrasound elicitation. Experiments 3, 4, and 5 indicated that the ultrasound-eliciting factor is relatively nonvolatile and heat resistant, although extreme heat will destroy its activity. The results of Experiments 6,7,8, 9, and 12 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 22 publications
2
60
1
Order By: Relevance
“…As expected from previous observations (e.g. Nyby et al, 1979), introducing female odor increased the vocal rate of individual males (Solo-no-odor versus Solo-female-odor: P adj =0.0066, W=240.50; Fig. 1C).…”
Section: Male Proximity Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…As expected from previous observations (e.g. Nyby et al, 1979), introducing female odor increased the vocal rate of individual males (Solo-no-odor versus Solo-female-odor: P adj =0.0066, W=240.50; Fig. 1C).…”
Section: Male Proximity Analysissupporting
confidence: 91%
“…In the absence of other social partners, female odor is required to elicit vocalizations from male mice (Nyby et al, 1979). This has led to the belief that these vocalizations are directed at the female and that they play a role in male-female interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Male mice begin vocalizing soon after presentation with a female, and even in response to the odor of female secretions or urine (Nyby et al, 1979;Byatt and Nyby, 1986). Female mice also prefer to be near speakers broadcasting male vocalizations relative to silent speakers in the first few minutes after playback, a preference not shown for other types of sounds (Hammerschmidt et al, 2009;Shepard and Liu, 2011).…”
Section: Fluctuation Of Serotonin: the Consequences For Auditory Procmentioning
confidence: 99%
“…Several authors have demonstrated that female mice odours and proceptive behaviours influence male calling behaviour (Whitney et al 1974;Nyby et al 1977Nyby et al , 1979. However, it is still not clear whether the female mouse's sexual cycle modifies the amount of vocalizations and/or the characteristics of calls emitted.…”
Section: Introductionmentioning
confidence: 99%